Students' Learning Needs Analysis in Learning English at SMAN 1 Campalagian Polewali Mandar - Bt Ibrahim, Hernawati; Nur, Rafiah; Ammade, Salasiah (LETS: Journal of Linguistics and English Teaching Studies, 2023)
In SMAN 1 Campalagian, many students are not receiving an education that meets their diverse learning needs, as many teachers continue to use a "one size fits all" approach that fails to accommodate individual needs. This "one size fits all" approach can negatively impact academic achievement. The aim of this research is to identify senior high school students’ learning needs, specifically learning interest. The method of the research was a mix-method, integrating quantitative and qualitative data. The instruments of the research were questionnaires, which consisted of closed-ended questions such as voting surveys for getting the quantitative data and open-ended questions for getting the qualitative data. The sample for this research were the students in the eleventh grade of SMAN 1 Campalagian. In analyzing the data, the researcher applied two kinds of techniques, including quantitative analysis and qualitative analysis. Based on the data analysis, the most preferred topics among the students were legends, fairy tales, and fables. For the interest areas, the most preferred areas were music, fine art, and historical sciences. Additionally, regarding the mode of expression, the most preferred expressions are written, oral, and design. The reasons they chose these preferences were various. The findings indicate that the students have a variety of learning interests with their own reasons. They showed interest in various topics areas and modes of expression.